Nucleotide Variation in Drosophila cryptochrome Is Linked to Circadian Clock Function: An Association Analysis - Pegoraro, Mirko; Sayegh Rezek, Emily; Fishman, Bettina; Tauber, Eran (Frontiers in Physiology, 2022)
Cryptochrome (CRY) is a conserved protein associated with the circadian clock in a broad range of organisms, including plants, insects, and mammals. In Drosophila, cry is a pleiotropic gene that encodes a blue light-dedicated circadian photoreceptor, as well as an electromagnetic field sensor and a geotaxis behavior regulator. We have generated a panel of nearly-isogenic strains that originated from various wild populations and which carry different natural alleles of cry. Sequencing of these alleles revealed substantial polymorphism, the functional role of which was elusive. To link this natural molecular diversity to gene function, we relied on association mapping. Such analysis revealed two major haplogroups consisting of six linked nucleotides associated with circadian phase (haplotypes All1/All2). We also generated a maximum-likelihood gene-tree that uncovered an additional pair of haplogroups (B1/B2). Behavioral analysis of the different haplotypes indicated significant effect on circadian phase and period, as well on the amount of activity and sleep. The data also suggested substantial epistasis between the All and B haplogroups. Intriguingly, circadian photosensitivity, assessed by light-pulse experiments, did not differ between the genotypes. Using CRISPR-mediated transgenic flies, we verified the effect of B1/B2 polymorphism on circadian phase. The transgenic flies also exhibited substantially different levels of cry transcription. We, moreover, analyzed the geographical distribution of the B1/B2 haplotypes, focusing on a 12 bp insertion/deletion polymorphism that differentiates the two haplotypes. Analysis of cry sequences in wild populations across Europe revealed a geographical cline of B1/B2 indel frequency, which correlated with seasonal bioclimatic variables. This spatial distribution of cry polymorphism reinforces the functional importance of these haplotypes in the circadian system and local adaptation.